Oesophagus / Esofago (C15.9) - Apoptotic frequencies are inversely related to levels of cell survival proteins in neoplastic development in patients with Barrett’s oesophagus - Eltahir, Zakaria; Jenkins, Gareth James Scott; Baxter, John Neville; Hopkins, Lynda; Griffiths, Anthony Paul (European Journal of Oncology and Environmental Health, 2014)
Purpose: We aimed here to assess the apoptotic cell frequency in Barrett’s oesophagus tissue and the histological series leading to adenocarcinoma. In parallel, we also aimed to quantify the expression of several anti-apoptotic proteins. The purpose was to assess the role of these anti-apoptotic proteins in apoptosis resistance across this well defined neoplastic series. Methods: Apoptotic bodies were manually counted in 74 biopsy tissue sections after robust training (and the use of CD45 and caspase 3 as internal controls). Immunohistochemistry was used to measure the expression of BCL-XL, XIAP and BCL-2 in a subset of the same sections. Results: Apoptotic frequency dropped from 0.2% in the Barrett’s oesophagus and low grade dysplasia groups to